The study on air pollution with nickel and vanadium in Croatia by using moss biomonitoring and ICP-AES - Vučković, Ivana; Špirić, Zdravko; Stafilov, Trajče; Kušan, Vladimir; Bačeva, Katerina (My University, 2013)
Moss samples were collected from 121 sampling sites all over Croatia during the summer and autumn of 2010. They were totally digested by using microwave digestion system and analysed by using atomic emission spectrometry with inductively coupled plasma (ICP-AES). Descriptive statistics and maps of distribution were made. The data obtained in this study were compared with those from the study in 2006 and additionally with the data obtained in the similar studies in neighbouring countries and Norway as pristine area. The median value of nickel is 3.16 mg kg(-1) and the content varies from 1.04 to 14.66 mg kg(-1). The content of vanadium ranges between 0.23 and 37.26 mg kg(-1) with the median value of 2.55 mg kg(-1). High contents of these elements are found in the vicinity of Rijeka, Zagreb and Sisak as a result of their emission from oil refinery, thermal power plant and industrial processes.